The Effectiveness of Using Movie Media on The Understanding of Learning Islamic Culture of Elementary School Students - Jajuli, Jajuli; Susilawati, Susilawati; Rahayu, Fanny Septiany; Pratama, Reza Rahman (Mimbar Sekolah Dasar, 2025)
The learning process of Islamic cultural history in elementary schools is often dominated by conventional methods such as lectures and textbook readings, which can lead to low student engagement, limited understanding, and reduced learning motivation. These challenges indicate the need for alternative instructional media that are more interactive and appealing to students. This study aims to measure the effectiveness of using movie media in improving students' cognitive understanding and self-efficacy in learning Islamic culture. This study uses a quantitative approach with a group pretest–posttest experimental design, conducted in three phases: pretest, treatment using movie media, and posttest to assess changes in students’ understanding and self-efficacy. Fifteen fourth- through sixth-graders made up the study's population. Pre- and post-test data show that the kids' learning outcomes have improved dramatically. After receiving therapy, which included of seeing an animated film on the life of Prophet Ayyub AS, the subjects' scores improved from 22 on the pretest to 23. experienced an average increase to 65. Therefore, movie learning media is effective in increasing elementary school students' understanding of Islamic cultural history. The implications of this research emphasize the potential of movie media as an effective alternative to traditional text-based methods in enhancing students’ understanding of Islamic cultural learning.